2018
DOI: 10.1093/neuros/nyy062
|View full text |Cite
|
Sign up to set email alerts
|

Nonawake vs Awake Placement of Spinal Cord Stimulators: A Prospective, Multicenter Study Comparing Safety and Efficacy

Abstract: Electrophysiological monitoring during asleep SCS implantation is a robust tool becoming more frequently used. This comparative prospective series demonstrates that asleep placement allows for shorter procedure and operating room times with superior paresthesia coverage profiles, while maintaining lower adverse events and equal clinical outcomes for pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 23 publications
3
49
2
Order By: Relevance
“…In addition, patients in whom wakeup testing during lead implantation would be difficult, such as those with poor cooperation or severe anxiety, would also benefit from asleep monitoring . Our mean operative time of 62 min is similar to previously reported surgical times with intraoperative wake‐up without use of IONM . Additional benefits include identification of physiologic midline and ventral/lateral placement.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, patients in whom wakeup testing during lead implantation would be difficult, such as those with poor cooperation or severe anxiety, would also benefit from asleep monitoring . Our mean operative time of 62 min is similar to previously reported surgical times with intraoperative wake‐up without use of IONM . Additional benefits include identification of physiologic midline and ventral/lateral placement.…”
Section: Discussionsupporting
confidence: 76%
“…Falowski et al 23 recently reported on a multicenter analysis of awake versus asleep placement of SCS leads. That was the only study to have performed a head-to-head comparison between the two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant differences were found for the operating time [88.9±51.2 minutes (mean±SD)] for the asleep procedures versus 125.2±39.7 minutes for the awake procedures) and the number of lead repositions (2.9±2.7 vs. 0.6±1.4 times), which Falowski et al 23 described as “…favoring the desire to have a more accurate placement.” Any new technique should produce results that are at least as good as the gold standard, which in this case is to place the leads in a patient who is awake or only minimally sedated. The data reported by Falowski et al 23 indicate not only some similar outcomes but also improved outcomes in key areas. It is interesting to note that the patients quality-of-life scores (as measured using MPQ and EQ-5D) were similar in the two groups while paresthesia coverage of the painful areas was significantly better in the asleep group (83.5±119.8%) than in the awake group (46.6±44.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The Neurostimulation Appropriateness Consensus Committee (NACC) guidelines recently stated that “Confirmation of correct lead placement has been advocated with either awake intraoperative confirmation of paraesthesia coverage or use of neuromonitoring in asleep placement, such as Electromyography (EMG) responses or Somatosensory evoked potential (SSEP) collision testing.” [38]. To date, there is only a single prospective, multicentre study comparing safety and efficacy of the neuromonitoring-assisted asleep SCS implantation technique as compared to conscious procedures [39]. The authors found that SCS placement under general anaesthesia was a shorter procedure with superior paraesthesia coverage profiles, while maintaining lower adverse events and equal clinical outcomes for pain relief compared to awake surgery.…”
Section: Technical Nuancesmentioning
confidence: 99%